The Seleukid royal economy : the finances and financial administration of the Seleukid empire - Aperghis, G. G. (Cambridge University Press, 2004)
This book examines the royal economy of the Seleukid Empire, the principal successor-state to the empire of Alexander the Greek. This wide-ranging economic study shows how rulers exploited resources to finance their administrations. Adopting a highly original numerical approach, the book presents a quantified model of the Seleukid royal economy.